2014
DOI: 10.14417/ap.575
|View full text |Cite
|
Sign up to set email alerts
|

Experiência da gravidez em situação de seropositividade para o VIH: Revisão da literatura brasileira

Abstract: Gerar um filho no contexto da seropositividade para VIH/Sida pode ser uma experiência emocionalmente difícil para as mulheres. No presente estudo, realizou-se uma revisão da literatura brasileira da última década (2000-2010) sobre a temática da experiência da gravidez em situação de seropositividade para VIH no Brasil, tendo-se identificado 20 estudos. Mais especificamente, objetivou-se identificar aspectos relevantes para futuras investigações e intervenções psicológicas junto a essa clientela. Os resultados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
5
0
4
Order By: Relevance
“…By indicating that life is at risk, the diagnosis threatens dreams and "contaminates" a whole universe of meanings and desires 24 . Anxiety is referred to as a sign of catastrophe, of physical and spiritual disintegration: "At first I thought I would look ugly, very thin, sick, bad..." (E1).…”
Section: What Am I Gestating: Life or Death? The Phase Of Existentialmentioning
confidence: 99%
See 1 more Smart Citation
“…By indicating that life is at risk, the diagnosis threatens dreams and "contaminates" a whole universe of meanings and desires 24 . Anxiety is referred to as a sign of catastrophe, of physical and spiritual disintegration: "At first I thought I would look ugly, very thin, sick, bad..." (E1).…”
Section: What Am I Gestating: Life or Death? The Phase Of Existentialmentioning
confidence: 99%
“…These thoughts are articulated and trigger other anxieties, linked to the abandonment of the child; the mother imagines herself as the provider of the child, but unable to see them grow. As a consequence, the woman fears for the child's helplessness and for her own end 24 : "It meant that my life was over..." (E3).…”
Section: What Am I Gestating: Life or Death? The Phase Of Existentialmentioning
confidence: 99%
“…Regarding the HIV, 542 cases were diagnosed, out of which 216 were female. 8 A study carried out in a reference center in Maceió city indicated a high prevalence of HIV vertical transmission, corresponding to a rate of 6.6%. 9 The regular notification of HIV infection cases from the confirmation of diagnosis came into force through Ministerial Ordinance No.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, no âmbito da gestação na presença do HIV, uma revisão recente da literatura brasileira mostrou que esta vivência pode ser especialmente difícil paras as mulheres, sendo permeada por maiores dificuldades de adaptação e emergência de preocupações sobre a TARV e, essencialmente, sobre a transmissão do HIV ao bebê (Levandowski et al, 2014). Porém, a literatura também tem evidenciado resultados positivos, indicando a gravidez como um motivo de orgulho para as mães adolescentes (Cerqueira-Santos, Paludo, Dei Schirò, & Koller, 2010) e a maternidade como uma força motivadora, uma demonstração de vida e de "normalidade" para as mulheres soropositivas, o que auxilia tanto na assimilação do diagnóstico quanto na adesão à TARV pessoal e do bebê (Sandelowski & Barroso, 2003).…”
Section: Introductionunclassified